2019
DOI: 10.1111/lam.13172
|View full text |Cite
|
Sign up to set email alerts
|

Identity and virulence properties of Aeromonas isolates from healthy Northern snakehead ( Channa argus ) in China

Abstract: Members of the genus Aeromonas are opportunistic pathogen of a variety of aquatic animals that exhibits multidrug resistance, phenotypes, virulence genes and virulence. The present study described the species distribution and the potential pathogenicity of Aeromonas isolated from healthy Northern snakehead (Channa argus) in China. Molecular identification revealed that A. veronii biovar veronii (69/167; 41·3%) and A. hydrophila (41/167; 24·6%) were the most common species found in Northern snakehead intestine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 44 publications
1
18
0
Order By: Relevance
“…In recent years, there have been an increasing numbers of cases of large-scale A. veronii outbreaks. It has been reported that A. veronii can infect freshwater fish, amphibians, birds, and red meat animals, resulting in serious losses to the aquaculture industry and threatening food safety [2][3][4]. In addition, A. veronii can also cause human infections, especially in elderly and children with low immunity, causing sepsis, gastroenteritis, and other diseases [5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, there have been an increasing numbers of cases of large-scale A. veronii outbreaks. It has been reported that A. veronii can infect freshwater fish, amphibians, birds, and red meat animals, resulting in serious losses to the aquaculture industry and threatening food safety [2][3][4]. In addition, A. veronii can also cause human infections, especially in elderly and children with low immunity, causing sepsis, gastroenteritis, and other diseases [5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…There has been a variety of proven virulence factors, including outer membrane proteins, motility related factors, toxins, proteases, quorum sensing systems, secretion systems, and iron ion acquisition systems, among others [16,17]. Related research demonstrated that hemolytic and cytotoxic activities and pathogenicity were correlated with the presence of virulence genes in Aeromonas strains [4]. Those virulence factors play an important role in the development of disease.…”
Section: Introductionmentioning
confidence: 99%
“…The pellets were washed three times with PBS. For the pH tolerance test, the washed pellets were resuspended in PBS at different pH values (3,4,5,6,7,8,9, and 10) at 28 • C. For the oxidative stress test, the washed pellets were resuspended in PBS containing 1 mM H 2 O 2 for 1 h at 28 • C. For the temperature stress test, the washed pellets were incubated in PBS for 1 h at 55 • C. For the osmotic tolerance test, the washed bacteria were plated directly on an LB solid plate containing 0.4 M NaCl at 28 • C for 24 h, after which colonies were counted. The pellets were resuspended 1 mL of sterile PBS for 1 h at 28 • C and regarded as blank controls in all tolerance tests.…”
Section: Stress Testmentioning
confidence: 99%
“…In recent years, a growing number of cases of large-scale A. veronii outbreaks have resulted in the infection of freshwater fish, livestock, birds, and red meat animals (such as camels). These events can cause severe losses to the breeding industry and threaten food hygiene and safety [2][3][4]. Moreover, A. veronii has been reported to be the etiological agent of gastrointestinal infections and a wide spectrum of extra-intestinal infections, including wound infection, septicemia, urinary tract and soft tissue infections, and septic arthritis in humans [5].…”
Section: Introductionmentioning
confidence: 99%
“…6 While causing substantial economic losses in the aquaculture industry, it also seriously threatens human health. 3,5,7 Reports of A. veronii cases are increasing, and related studies show that its pathogenicity is influenced by multiple factors. 3 However, current research on A. veronii is aimed mainly at studying common virulence factors, such as outer membrane proteins, pili, flagella, aerolysin, hemolysin, enterotoxin, proteases, and some adhesion factors, so pathogenesis has not completely been characterized.…”
Section: Introductionmentioning
confidence: 99%